A produção científica e a enfermagem ocupacional - SOUZA, Maria do Socorro Batista de (2016)
It studies the scientifical production in the area of Occupational Nursing during the period 1941 - 1986. It informs about changes that have occurred along the history of Nursing. It selects bibliographic material for research and carries out a survey of scientifical production on Ocupational Nursing. It shows the for diffusion and approach of knowledge in the area of Occupational Nursing.